2002
DOI: 10.4049/jimmunol.169.11.6085
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Effector T Cells In Vivo Is Determined During Activation and Differs for CD4+ and CD8+ Cells

Abstract: Effector T cells generated in the mesenteric lymph nodes (mLN) are known to accumulate in mLN and the tissue drained by them after circulating in the blood. Their accumulation is due less to preferential entry into mLN but more to preferential proliferation within mLN. The factors regulating the proliferation of effector T cells in vivo are unclear, and it is unknown whether they are different for CD4+ and CD8+ effector T cells. Rat T cells from mLN or peripheral lymph nodes (pLN) were stimulated polyclonally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Rats from the standard inbred strain LEW/Ztm (RT.7 a ) and the congenic strain LEW.7B/Won (RT.7 b ) were used (11). Cell suspensions were prepared from peripheral lymph nodes (pooled axillary, brachial, and cervical lymph nodes) and mesenteric lymph nodes of LEW.7B rat.…”
Section: In Vitro Generated Effector T Cellsmentioning
confidence: 99%
“…Rats from the standard inbred strain LEW/Ztm (RT.7 a ) and the congenic strain LEW.7B/Won (RT.7 b ) were used (11). Cell suspensions were prepared from peripheral lymph nodes (pooled axillary, brachial, and cervical lymph nodes) and mesenteric lymph nodes of LEW.7B rat.…”
Section: In Vitro Generated Effector T Cellsmentioning
confidence: 99%
“…Therefore, the milieu experienced during generation determines the subsequent proliferative responsiveness of effector T cells also in vivo. Effector T cells generated in rat mLN maintain their preferential proliferative responsiveness to TGF-g 1 for at least 50 days [17].…”
Section: Discussionmentioning
confidence: 99%
“…First, it is well known that, for example, DC from mucosal sites and pLN differ in many aspects [18,19]. Secondly, effector mLN T cells making contact with mLN DC in vivo have a proliferation rate twice as high as those which are not in contact with DC [17]. Further studies are needed in the rat to characterize Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both approaches the local information is missing because in cell suspensions, the cells interact randomly with each other, and homogenates of whole lymphoid organs reflect the average expression of genes only. However, even with these approaches, it was shown that peripheral lymph nodes mainly draining the skin have a Th1-dominated cytokine milieu, whereas mesenteric lymph nodes (mln) 3 mainly draining the intestine reveal a Th2-dominated milieu (9,10). Today, cells and tissues can be analyzed in their original environment using laser microdissection (11)(12)(13).…”
Section: A Ctivated Cd4mentioning
confidence: 99%